Accelerated non-medical endoscopy training: one trust's experience. (2nd September 2019) - Donnelly, Leigh; Bone, Barbara; Kennair, Trudi
Abstract : Endoscopy services are under considerable pressure to meet the increasing demand expected by 2020. A large hospital foundation trust was offered the opportunity to develop its endoscopy workforce by two of its endoscopy nurses obtaining a place on Health Education England's accelerated non-medical endoscopy training programme. The training took place over a period of 7 months and combined comprehensive endoscopy training supported by a robust academic component. A thematic analysis was carried out on the trainees' reflective journals kept during the course, and this highlighted the frequently occurring themes. The trust has benefited greatly from the experience, and, although challenging, the rewards can be far-reaching and have a positive impact on staff and patients.